THE IMPACT OF NATIONAL FOODS SOUTH AFRICA ON FOOD WASTE MANAGEMENT - MOTSHABI, BONOLO (The IIE, 2021)
The paper sought to determine the effectiveness of National Foods South Africa on food waste management. The paper was premised on the underlying assumption that there is a challenge of food waste management that is affecting organisations and the economy, thus the need to understand the increased importance of managing food waste in the contemporary environment. The study utilised the qualitative research approach where the perceptions, attitudes and experiences of participants were utilised to have an informed understanding on the research problem. Through purposive sampling where key informants were selected, the study utilised semi-structured interviews with the aim of digging deep and getting informed responses. From thematic analysis as the data analysis method, the study identified food handling challenges, infrastructural challenges and technological challenges as the challenges faced by National Foods South Africa on food waste management. The study also discovered that consumers are an important base in food waste management as consumers are the end products in the food waste management supply chain. Therefore, consumers need to effectively understand their role in food waste management, and National Foods South Africa needs to come up with methods such as advertising and awareness campaigns to ensure that consumers have effective knowledge and take part in food waste management. The study also identified that both the management and employees at National Foods South Africa have a role to play in enhancing food waste management, and this can be achieved through training and development of employees as well as management concerning itself with the adoption of technological advancements for improved food waste management. The recommendations from the study therefore include improvement in infrastructure and investment in improving consumer attitudes on food waste management as methods that can be utilised to further enhance food waste management at National Foods South Africa.
Keywords: Food waste management supply chain; Consumer perception; Food processing; Food loss and waste management